Inhibitory Effect of Natural Anti-Inflammatory Compounds on Cytokines Released by Chronic Venous Disease Patient-Derived Endothelial Cells. (31st December 2013) - Tisato, Veronica; Zauli, Giorgio; Rimondi, Erika; Gianesini, Sergio; Brunelli, Laura; Menegatti, Erica; Zamboni, Paolo; Secchiero, Paola
Abstract : Large vein endothelium plays important roles in clinical diseases such as chronic venous disease (CVD) and thrombosis; thus to characterize CVD vein endothelial cells (VEC) has a strategic role in identifying specific therapeutic targets. On these bases we evaluated the effect of the natural anti-inflammatory compounds α -Lipoic acid and Ginkgoselect phytosome on cytokines/chemokines released by CVD patient-derived VEC. For this purpose, we characterized the levels of a panel of cytokines/chemokines (n = 31 ) in CVD patients' plasma compared to healthy controls and their release by VEC purified from the same patients, in unstimulated and TNF- α stimulated conditions. Among the cytokines/chemokines released by VEC, which recapitulated the systemic profile (IL-8, TNF- α, GM-CSF, INF- α 2, G-CSF, MIP-1 β, VEGF, EGF, Eotaxin, MCP-1, CXCL10, PDGF, and RANTES), we identified those targeted by ex vivo treatment with α -Lipoic acid and/or Ginkgoselect phytosome (GM-CSF, G-CSF, CXCL10, PDGF, and RANTES). Finally, by investigating the intracellular pathways involved in promoting the VEC release of cytokines/chemokines, which are targeted by natural anti-inflammatory compounds, we documented that α -Lipoic acid significantly counteracted TNF- α -induced NF-κ B and p38/MAPK activation while the effects of Ginkgo biloba appeared to be predominantly mediated by Akt. Our data provide new insights into the molecular mechanisms of CVD pathogenesis, highlighting new potential therapeutic targets.